Discussion of the Current Treatment Methods for Degenerative Lumbar Spondylolisthesis - Ma, Chenxi; Su, Xiaoqiang (Journal of Contemporary Medical Practice, 2024)
Degenerative spondylolisthesis (DS) is caused by degeneration that causes the lumbar vertebral body of the diseased segment to be displaced relative to the lower vertebral body, which is usually forward, and is not accompanied by pedicle fracture or defect, also known as "pseudospondylolisthesis". DS is more common in the L4/L5 segment, followed by the L3/L4 and L5/S1 segments, and is mostly mild slippage of the first and second degrees [2-4]. At present, the pathogenesis of DS is not fully understood, and it may be related to age-related degeneration of supporting structures, such as intervertebral discs, facet joints, bones, ligaments, facet capsule, and paravertebral muscles. In addition, the decrease in estrogen in women is also associated with the development of DS [1]. Clinically, DS is characterized by recurrent symptoms such as low back and leg pain, numbness of the lower limbs, intermittent claudication, and in severe cases, colorectal symptoms may occur [4].